Penentuan Prioritas Perbaikan Jalan Berbasis Metode Analytic Network Process Sebagai Komponen Menuju Kota Cerdas - Wahyul Amien Syafei; Kusnadi Kusnadi; Bayu Surarso (Universitas Diponegoro, 2016)
Smart city become a demand for people to live in more comfort and easier. Knowledge is needed in every decision support system in smart city. This paper presents a research in determining the priority order of road handling based on level of service by using Analytic Network Process which is implemented into decision support systems as a component toward smart city. Variables used refers to the Highway Capacity Manual Indonesia based on the volume of traffic and the road characteristic data. Analytic Network Process is used because of its advantages in conducting multi-criteria assessment on the basis of the subjective judgment of decision makers and can combine quantitative and qualitative data. From the results of the validation test between the system output and outcome data field issued by Dishubinkom Cirebon, the accuracy of the test results of 10 streets in the city of Cirebon with validation test Spearman Rank correlation is equal to 0.867. The results showed Analytic Network Process can be implemented and an appropriate solution in determining the road handling priority.